(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
Groundnut Shell (GS) and Sorghum Husk (SH) were utilised as adsorbents for the adsorption of Congo Red dye. The adsorbent underwent proximate analysis and was characterised using Fourier transform infrared spectroscopy (FTIR). The effects of several experimental conditions on the adsorption extent were studied, including initial dye concentration and contact time. Spectrophotometry was used to determine the dye concentration. The equilibrium data was represented using the Langmuir, Freundlich, Temkin and Harkins, and Jura models. The Freundlich model represented the equilibrium data for Congo Red with GS better than SH. The maximal adsorption capacity of GS was determined to be 4.3660 mg/g, while SH was less efficient. The pseudo-first and pseudo-second-order kinetic equations, power function, and Elovich models were used to model adsorption data. The pseudo-second-order kinetic equation was found to best represent the sorption kinetics for all adsorption processes, as qe experimental and qe theoretical are nearly identical.